PKM: MENINGKATKAN LITERASI MELALUI STRATEGI BINCANG NUMERASI BAGI SEKOLAH YANG NILAI NUMERASINYA MASIH RENDAH DI KABUPATEN BADUNG - I Dewa Putu Juwana; I Ketut Muada; Ni Made Pira Erawati; Dewa Ayu Widiasri; I Ketut Lanus; Ni Wayan Dian Permana Dewi (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
This Community Service (PkM) activity aims to improve the numeracy literacy of elementary school students who still show low achievement in numeracy assessments, especially in Badung Regency. One of the strategies implemented is